Glass cloth, prepreg and printed wiring board

By adjusting the Fe and F content in the glass cloth, the problem of the decrease in the strength of the glass cloth after heat treatment is solved, and a glass cloth with low dielectric constant and high fracture resistance is achieved, which is suitable for the preparation of stable pre-prepared materials and printed circuit boards.

JP2025039605AInactive Publication Date: 2025-03-21ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024231558
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The strength of the existing low-dielectric constant glass cloth is significantly reduced during the heat treatment process, resulting in the easy breakage of the glass cloth, affecting the production process of preparing pre-prepared materials and printed circuit boards.

Method used

By adjusting the Fe content in the glass cloth, ensure that it remains between 0.1% and 0.4% after heat treatment, and adjusting the F content if necessary to suppress the phenomenon of strength reduction.

Benefits of technology

While maintaining a low dielectric constant, it is possible to reduce the strength of the glass cloth and improve the break resistance of the glass cloth, thereby stably preparing pre-prepared materials and printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039605000001
    Figure 2025039605000001
  • Figure 2025039605000002
    Figure 2025039605000002
Patent Text Reader

Abstract

To provide a low dielectric glass cloth with strength degradation suppressed, and a prepreg and a printed wiring board made of the low dielectric glass cloth.SOLUTION: A glass cloth including a glass yarn made of a plurality of glass filaments as warp and weft has a weight loss factor obtained as a product of a weight loss ratio derived from the glass component in heat treatment at 380°C for 2 hours and an average radius of the glass filament in the following equation (1) of 0.18 or more and 0.45 or less. The glass cloth has an Fe content in terms of Fe2O3 of more than 0.1 mass% and less than 0.4 mass%. The weight loss factor=Weight loss ratio (%)×Average radius of the glass filament (μm) ... (1)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass cloth, a prepreg, and a printed wiring board. [Background technology]

[0002] With the recent development of the information and communication society, data communication and / or signal processing have become large-volume and high-speed, and the dielectric constant of printed wiring boards used in electronic devices has been significantly reduced. For this reason, many low-dielectric glass cloths have been proposed as glass cloths for use in printed wiring boards.

[0003] For example, the low dielectric glass cloth disclosed in Patent Document 1 achieves a low dielectric constant by incorporating a large amount of B2O3 into the glass composition, as compared to the E-glass cloth that has been commonly used conventionally, while at the same time adjusting the amounts of other components such as SiO2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-292567 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when the B2O3 content in the glass yarn is increased to lower the dielectric constant of the glass cloth, the elastic modulus of the glass yarn is reduced, and furthermore, the strength of the glass cloth is significantly reduced by heat treatment such as desizing agent treatment performed during the manufacturing process. Therefore, there is a problem that the glass cloth is easily broken. When such a glass cloth is used to manufacture a prepreg, the glass cloth breaks in situations where an external load is applied to the glass cloth, such as an operation to control the amount of resin attached, causing a production problem.

[0006] Regarding this point, Patent Document 1 discloses a method of suppressing the volatilization of B2O3 by setting the B2O3 content to less than 20 mass% and the CaO content to a specified range during spinning of glass yarn. However, setting the B2O3 content to less than 20 mass% does not fully meet the demand for low dielectric constant, and ultimately, a glass cloth with low dielectric constant and suppressed strength reduction has not been realized. Furthermore, it has been found that when the weight loss due to heat treatment is within a specific range, the strength reduction becomes more serious.

[0007] The present invention has been made in consideration of the above problems, and has an object to provide a low dielectric glass cloth in which deterioration in strength is suppressed, and a prepreg and a printed wiring board using the low dielectric glass cloth. [Means for solving the problem]

[0008] As a result of intensive research into solving the above problems, the inventors have found that the above problems can be solved by adjusting the Fe content in a glass cloth having a predetermined weight loss tendency, and have thus completed the present invention.

[0009] That is, the present invention is as follows. [1] A glass cloth constructed by using glass yarns made of a plurality of glass filaments as warp yarns and weft yarns, In the following formula (1), a weight loss coefficient calculated as the product of the weight loss rate derived from the glass component in a heat treatment at 380° C. for 2 hours and the average radius of the glass filaments is 0.18 or more and 0.45 or less, Weight reduction coefficient=weight reduction ratio (%)×average radius of the glass filaments (μm) (1) The Fe content of the glass cloth is more than 0.1 mass% and less than 0.4 mass% in terms of Fe2O3. Glass cloth. [2] The Fe content of the glass cloth is more than 0.2 mass% and less than 0.4 mass%, calculated as Fe2O3. The glass cloth according to [1]. [3] The Fe content of the glass cloth is more than 0.3 mass% and less than 0.4 mass%, calculated as Fe2O3. The glass cloth according to [2]. [4] The F content of the glass cloth is more than 0.005% by mass and less than 0.4% by mass. The glass cloth according to any one of [1] to [3]. [5] The F content of the glass cloth is more than 0.005% by mass and less than 0.2% by mass. The glass cloth according to [4]. [6] The F content of the glass cloth is more than 0.005% by mass and less than 0.1% by mass. The glass cloth according to [5]. [7] The glass cloth, The Si content is 40 to 60 mass% in terms of SiO2, The B content is 15 to 30 mass% calculated as B2O3. The glass cloth according to any one of [1] to [6]. [8] The glass cloth, The Al content is 10 to 20 mass% calculated as Al2O3, The Ca content is 4 to 12 mass% in terms of CaO, The Mg content is 1% by mass or less in terms of MgO. The glass cloth according to [7]. [9] The elastic modulus of the glass cloth is 50 to 70 GPa. The glass cloth according to any one of [1] to [8].

[10] The elastic modulus of the glass cloth is 50 to 63 GPa. The glass cloth according to [9]. [1] The average diameter of the glass filaments constituting the warp and weft yarns is independently 3.5 to 5.4 μm. The glass cloth according to any one of [1] to

[10] .

[12] Has a dielectric constant of 5.0 or less at a frequency of 1 GHz; The glass cloth according to any one of [1] to

[11] .

[13] [1] to

[12] , and and a matrix resin impregnated in the glass cloth. Prepreg.

[14] The glass cloth according to any one of [1] to

[12] is provided. Printed wiring board. Effect of the Invention

[0010] According to the present invention, it is possible to provide a low dielectric glass cloth in which a decrease in strength is suppressed, and a prepreg and a printed wiring board using the low dielectric glass cloth. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Below, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail, but the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0012] [Glass cloth] The glass cloth of the present embodiment is a glass cloth constituted of glass yarns each consisting of a plurality of glass filaments as warp and weft yarns, in which a weight reduction coefficient calculated as the product of the weight reduction rate derived from the glass component in a heat treatment at 380°C for two hours and the average radius of the glass filaments in the following formula (1) is 0.18 or more and 0.45 or less, and the Fe content of the glass cloth is more than 0.1 mass% and less than 0.4 mass%, calculated as Fe2O3. Weight reduction coefficient = weight reduction ratio (%) × average radius of glass filaments (μm) (1)

[0013] In glass cloth having a low dielectric constant, the strength of the glass threads decreases during heat treatment in the manufacturing process or in a subsequent heat treatment. This strength decrease and the low elastic modulus of the glass threads constituting the low dielectric glass cloth make the low dielectric glass cloth more susceptible to breakage than those using other glass threads such as E glass. In this embodiment, the strength decrease due to heat treatment is suppressed by adjusting the Fe (iron) content in the glass, and more preferably the F (fluorine) content, in the glass loss having a predetermined weight loss tendency.

[0014] The reason why the strength reduction can be suppressed by adjusting the Fe content is not limited, but is considered to be as follows. During spinning, even if the glass component volatilizes under high temperature conditions and a sparse portion occurs in the glass thread, the molten glass can flow to fill the portion, and the portion where the glass thread becomes sparse due to the volatilization of the glass component accompanied by weight loss can be eliminated by this flow. On the other hand, even if a sparse portion occurs due to the volatilization of the glass component in the glass cloth, the glass cannot flow to fill the portion. Under this circumstance, in the glass cloth of the present embodiment, it is considered that Fe may act to hold together the portion where the glass thread becomes sparse due to the volatilization of the glass component.

[0015] In addition, the reason why the strength reduction is further suppressed by adjusting the F content is not limited, but is considered to be as follows. F reduces the viscosity of molten glass in the glass manufacturing process. Therefore, when the F content is within a predetermined range, metal components such as Fe are uniformly dispersed without localization when they are incorporated into the glass structure, and uniform glass can be formed. It is considered that the effect of Fe connecting the parts where the glass threads become sparse due to the volatilization of the above-mentioned glass components is more effectively expressed by Fe being uniformly dispersed. In addition, it is considered that if hard parts are unevenly distributed in the glass due to the localization of Fe, etc., it is likely that breakage will occur starting from those parts, but it is considered that such localization can be alleviated by adjusting the F content, and the strength reduction can be further suppressed.

[0016] By having the above-mentioned configuration, the present embodiment can solve the breakage problem that the low dielectric glass cloth has, and can provide a glass cloth having high breakage resistance and a low dielectric constant. The configuration of the present embodiment will be described in more detail below.

[0017] (Weight reduction coefficient) The weight reduction coefficient (hereinafter, also simply referred to as "weight reduction coefficient") calculated as the product of the weight reduction rate derived from the glass component and the average radius of the glass filaments when the glass cloth is heat-treated at 380°C for 2 hours is 0.18 or more and 0.45 or less, preferably 0.19 or more and 0.42 or less, more preferably 0.20 or more and 0.39 or less, and even more preferably 0.20 or more and 0.35 or less.

[0018] "Weight loss ratio derived from glass components" means that the weight loss ratio in the case of heat treatment at 380°C for 2 hours is due to the disappearance of glass components due to volatilization during heat treatment. As described later, in the present embodiment, when a surface treatment agent such as a silane coupling agent is attached to the glass cloth or when a large amount of organic impurities is attached, the weight loss ratio is calculated after removing the surface treatment agent such as a silane coupling agent or the organic impurity attached components that are physically adsorbed with a good solvent such as alcohol or acetone. Therefore, the weight loss ratio of the glass cloth after heat treatment after removing the attached components that are decomposed by heat at 380°C is the weight loss ratio derived from the glass components.

[0019] It was also confirmed that the weight reduction rate depends on the filament diameter of the glass yarn. The weight reduction rate varies depending on the glass filament diameter, and the smaller the filament diameter, the greater the weight reduction amount. On the other hand, the product of the weight reduction rate and the filament radius is an almost constant value regardless of the filament diameter. Therefore, in this embodiment, the weight reduction coefficient is standardized by the filament diameter.

[0020] A weight reduction coefficient of 0.18 or more is likely to cause a decrease in strength if left as is. However, in this embodiment, the decrease in strength can be suppressed by adjusting the Fe content, which will be described later, and more preferably, the F content, and a glass cloth having a lower dielectric constant can be obtained from the composition of the glass cloth. In addition, a weight reduction coefficient of 0.45 or less allows the effect of Fe in suppressing the decrease in strength to be effectively acted upon, and a significant decrease in strength can be suppressed.

[0021] The weight loss ratio can be measured by the following procedure. First, the glass cloth is placed in a dryer at 105°C ± 5°C and dried for 60 minutes, then the glass cloth is transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth is measured to the nearest 0.1 mg (glass cloth weight a). Next, the glass cloth is heated at 380°C for 2 hours, then the glass cloth is transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth is measured to the nearest 0.1 mg (glass cloth weight b after heat treatment). The weight lost due to the heat treatment is then determined, and the weight loss ratio (%) is calculated using the following formula (2). Weight reduction rate (%) = (ab) / a×100 ···(2)

[0022] The weight loss ratio obtained as described above is preferably 0.04 to 0.5%, more preferably 0.05 to 0.3%, and further preferably 0.06 to 0.25%. When the weight loss ratio is 0.04% or more, strength loss is likely to occur as it is. However, in this embodiment, the strength loss can be suppressed by adjusting the Fe content described later, and more preferably, the F content, and also a glass cloth having a lower dielectric constant can be obtained from the composition of the glass cloth. Furthermore, when the weight loss ratio is 0.5% or less, the effect of Fe in suppressing the strength loss is effectively acted on, and a significant strength loss can be suppressed.

[0023] Next, the average diameter of the glass filaments of the glass yarn constituting the glass cloth is measured in accordance with JIS R3420, and the average filament radius is calculated as half of the filament diameter. In this embodiment, when simply referring to glass filaments, it means glass monofilaments. The average radius of the glass filaments used in calculating the weight reduction coefficient is the average radius before the heat treatment. The average radius of the glass filaments thus calculated is preferably 1.25 to 4.5 μm, more preferably 1.5 to 3.75 μm, and even more preferably 1.75 to 2.7 μm.

[0024] The glass cloth used in the above-mentioned method for measuring the weight loss rate can be appropriately pretreated. For example, the glass cloth unwound from the intermediate roll after desizing (heat cleaning) has no attached matter on the glass filaments, and can be used as is in the above-mentioned method for measuring the weight loss rate.

[0025] On the other hand, when determining the weight reduction ratio for glass cloth to which a surface treatment agent such as a silane coupling agent has been applied, the physically adsorbed surface treatment agent such as the silane coupling agent can be washed away in advance with a good solvent such as alcohol or acetone, and then the weight reduction coefficient can be determined by the above method.

[0026] The term "physically adsorbed silane coupling agent" refers to a silane coupling agent that is attached to the glass filament, but is not a silane coupling agent that is bonded to the glass filament by a chemical bond. In contrast, a silane coupling agent that is bonded to the glass filament by a chemical bond is called a "chemically adsorbed silane coupling agent."

[0027] In addition, when the glass cloth contains organic impurities (such as a starch-based sizing agent applied during the glass yarn manufacturing process, or combustion residues in the heat cleaning process of the sizing agent), the weight reduction coefficient can be determined by the above method after removing the organic impurities adhering to the glass cloth in advance by a cleaning removal operation using alcohol, acetone, or the like.

[0028] The above-mentioned washing is to remove physically adsorbed silane coupling agent and organic impurities, and is not to remove chemically adsorbed silane coupling agent.However, even if heated at 380°C for 2 hours, chemically adsorbed silane coupling agent does not decompose, and even if a part of it decomposes, it does not exceed the error range, so in the measurement of weight loss rate in this embodiment, it is not necessary to remove chemically adsorbed silane coupling agent by pretreatment.

[0029] From the viewpoint of simplifying the decision as to whether or not to perform pretreatment, the glass cloth may be uniformly washed in advance with a good solvent such as alcohols, acetone, etc. for the measurement of the weight loss ratio. This allows the weight loss ratio to be measured under the same conditions, even if the glass cloth is pulled out from the intermediate roll after desizing treatment (heat cleaning) or has physically adsorbed silane coupling agent or organic impurities attached thereto.

[0030] As another method, when determining the weight loss coefficient, the amount of the surface treatment agent and organic impurities before and after heating are quantified, and the weight loss caused by the surface treatment agent is subtracted from the weight loss obtained to determine the weight loss coefficient derived from the glass component. As a method for determining the weight loss caused by the surface treatment agent, a known method such as the method for quantifying the amount of a silane coupling agent described in Japanese Patent No. 6472082 may be used.

[0031] The weight loss coefficient can be adjusted by increasing or decreasing a relatively volatile component in the composition of the glass cloth, such as the B content, and from a similar viewpoint, it can also be adjusted by increasing or decreasing other components.

[0032] In addition, the weight reduction coefficient can also be adjusted by increasing or decreasing the frequency with which the glass surface is exposed to a high-temperature atmosphere, by adjusting the spatial filling rate of glass in the glass cloth (weaving density or thickness), adjusting the degree of unraveling of the monofilaments constituting the glass yarn bundle by fiber-opening processing or the like, adjusting the monofilament diameter of the glass yarn used, and so on. That is, the weight reduction coefficient is not determined only by the composition of the glass cloth.

[0033] (composition) The composition of the glass cloth of this embodiment will be described below. The composition of the glass cloth is synonymous with the composition of the glass yarn constituting the glass cloth. In the composition of the glass cloth of this embodiment, the Fe content is more than 0.1 mass% and less than 0.4 mass%, preferably more than 0.2 mass% and less than 0.4 mass%, more preferably more than 0.3 mass% and less than 0.4 mass%, and most preferably more than 0.3 mass% and 0.38 mass% or less, calculated as Fe2O3. When the Fe content exceeds 0.1 mass%, it is possible to suppress a decrease in strength due to heat treatment of the glass cloth. In addition, when the Fe content is less than 0.4 mass%, it is possible to suppress a decrease in strength of the glass cloth itself before heat treatment due to an excessive Fe content. The Fe content can be adjusted depending on the amount of raw material used for producing the glass filaments, or by refining, removing, or adding during the production of the glass filaments.

[0034] The decrease in strength due to an excessive Fe content is not particularly limited, but is considered to be as follows. The glass yarn is basically composed of amorphous parts, but the parts in which Fe is present can be considered to be parts with relatively high crystallinity. It is considered that the existence of highly crystalline parts causes parts with locally weak strength to become apparent, but in this embodiment, the decrease in strength of the glass cloth can be suppressed by adjusting the Fe content to a certain amount or less.

[0035] The F content in the composition of the glass cloth of this embodiment is preferably more than 0.005% by mass and less than 0.4% by mass, more preferably more than 0.005% by mass and less than 0.2% by mass, and even more preferably more than 0.005% by mass and less than 0.1% by mass. When the F content exceeds 0.005% by mass, the decrease in strength of the glass cloth due to the heat treatment tends to be more suppressed. When the F content is less than 0.4% by mass, it is possible to suppress the decrease in strength of the glass cloth itself before the heat treatment due to the F content being too high. The F content can be adjusted according to the amount of raw material used to prepare the glass filaments.

[0036] The decrease in strength due to an excessive F content is not particularly limited, but is believed to be due to the following: As the F content increases, the phase separation of the glass composition becomes stronger, making it more difficult to homogenize the glass components.

[0037] In a preferred aspect of this embodiment, by setting both the Fe content and the F content within the above-mentioned predetermined ranges, the effect of suppressing the decrease in strength due to heat treatment tends to be further improved.

[0038] The Si content of the glass cloth is preferably 40 to 60 mass%, more preferably 45 to 55 mass%, further preferably 47 to 53 mass%, and even more preferably 48 to 52 mass%, calculated as SiO2. Si is a component that forms the skeletal structure of the glass yarn, and by having a Si content of 40 mass% or more, not only is the strength reduction caused by heat treatment suppressed, but the strength of the glass yarn itself before heat treatment is further improved, and breakage of the glass cloth tends to be further suppressed in the glass cloth manufacturing process and in the post-process such as the manufacturing of a prepreg using the glass cloth. In addition, by having a Si content of 40 mass% or more, the dielectric constant of the glass cloth tends to be further reduced. On the other hand, by having a Si content of 60 mass% or less, the viscosity at the time of melting is further reduced in the manufacturing process of the glass filament, and glass fibers with a more homogeneous glass composition tend to be obtained. Therefore, the resulting glass filaments are less likely to have parts that are easily devitrified or parts where it is difficult for bubbles to escape, and therefore the glass filaments are less likely to have parts that are locally weak in strength, and as a result, the glass cloth made of the glass yarn obtained by using the same is less likely to break. The Si content can be adjusted according to the amount of raw material used to produce the glass filaments.

[0039] The B content of the glass cloth is preferably 15 to 30 mass%, more preferably 17 to 28 mass%, further preferably 20 to 27 mass%, further more preferably 21 to 25 mass%, and further more preferably 21.5 to 24 mass%, calculated as B2O3. When the B content is 15 mass% or more, the dielectric constant tends to be lowered. When the B content is 30 mass% or less, the strength of the glass cloth is high and the moisture absorption resistance is excellent, which is preferable. In addition, when the B content is 30 mass% or less, the volatilization of glass components due to heat treatment such as desizing agent treatment is suppressed to a small extent, and the decrease in strength and the decrease in moisture absorption resistance are also suppressed, so that the insulation reliability tends to be improved. The B content can be adjusted according to the amount of raw material used in the production of the glass filaments. In addition, when the B content may vary during the production of the glass filaments, the amount of the raw material can be adjusted in advance in anticipation of the variation.

[0040] The glass cloth may have other compositions in addition to those described above. The other compositions are not particularly limited, but examples thereof include Al, Ca, Mg, P, Na, K, Ti, and Zn.

[0041] The Al content of the glass cloth is preferably 10 to 20 mass%, more preferably 11 to 18 mass%, and further preferably 12 to 17 mass%, calculated as Al2O3. When the Al content is within the above range, the electrical properties and strength tend to be improved. The Al content can be adjusted according to the amount of raw material used to prepare the glass filaments.

[0042] The Ca content of the glass cloth is preferably 4.0 to 12 mass%, preferably 5.7 to 10 mass%, and more preferably 6.0 to 9.0 mass%, calculated as CaO. When the Ca content is 4.0 mass% or more, the viscosity at the time of melting is further reduced in the manufacturing process of the glass filaments, and glass fibers having a more homogeneous glass composition tend to be obtained. Also, when the Ca content is 10 mass% or less, the dielectric constant tends to be further improved. The Ca content can be adjusted according to the amount of raw material used in manufacturing the glass filaments.

[0043] The Mg content of the glass cloth is preferably 1.0% by mass or less, more preferably 0.7% by mass or less, still more preferably 0.01% by mass or more and 0.7% by mass or less, even more preferably 0.05% by mass or more and 0.6% by mass or less, and even more preferably 0.05% by mass or more and 0.45% by mass or less, calculated as MgO. When the Mg content is 1.0% by mass or less, the glass cloth tends to be less likely to break when passing through a squeeze roll or nip roll in a wet state in a fiber opening process or a surface treatment process during glass cloth production. In addition, phase separation during glass filament production is suppressed, and the moisture absorption resistance of the obtained glass filament is further improved. As a result, the obtained printed wiring board is less susceptible to the influence of a high humidity environment, and the environmental dependency of the dielectric constant can be reduced. The Mg content can be adjusted according to the amount of raw material used in glass filament production.

[0044] The ratio of the Ca content to the Mg content is preferably 5.0 to 50, more preferably 10 to 45, even more preferably 15 to 40, still more preferably 20 to 35, and even more preferably 20 to 30. When the ratio of the Ca content to the Mg content is within the above range, a glass fiber having high strength and excellent moisture absorption resistance due to its more homogeneity can be obtained, breakage is less likely to occur, and the environmental dependency of the dielectric constant tends to be reduced.

[0045] The above contents can be measured by ICP atomic emission spectrometry. Specifically, the Si content and B content can be obtained by decomposing a weighed glass cloth sample with sodium hydroxide under pressure, dissolving it with dilute nitric acid, and filtering it. The insoluble matter is then melted with sodium carbonate, combined with the filtrate to a constant volume, and the obtained sample is measured by ICP atomic emission spectrometry.

[0046] The Fe content, Al content, Ca content, and Ma content can be obtained by decomposing a weighed glass cloth sample by heating with perchloric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, dissolving by heating with dilute aqua regia, and filtering the sample. The filtrate is made to a constant volume. The insoluble portion is then decomposed by heating with sulfuric acid, nitric acid, hydrochloric acid, and hydrogen fluoride to a constant solution, and the obtained sample is measured by ICP atomic emission spectrometry. The ICP atomic emission spectrometry can be performed using a PS3520VDD II manufactured by Hitachi High-Tech Science Corporation.

[0047] The F content can be measured by burning a weighed glass cloth sample in a tubular electric furnace and absorbing the generated gas into an absorbing solution. The fluoride ion (F-) in this solution can be measured by ion chromatography to determine the content in the sample. The combustion device can be an automatic sample combustion device (AQF-2100S) manufactured by Mitsubishi Chemical Analytech, and the measurement device can be an ion chromatograph ICS-1500 manufactured by Thermo Fisher Scientific.

[0048] The elastic modulus of the glass cloth is preferably 50 to 70 GPa, more preferably 50 to 63 GPa, and further preferably 53 to 63 GPa. The lower the elastic modulus of the glass cloth, the more likely it is to break. Therefore, when the elastic modulus is 50 GPa or more, in the glass cloth manufacturing process such as the opening process and the surface treatment process, the glass cloth tends to be less likely to break when it passes through a squeeze roll or a nip roll in a wet state. Also, in the post-process such as the manufacture of a prepreg, when the glass cloth is passed through a slit for the purpose of controlling the amount of resin impregnated into the glass cloth, the glass cloth tends to be less likely to break. When the elastic modulus of the glass cloth yarn is 70 GPa or less, the glass cloth has a soft texture, and when the glass cloth passes through a narrow gap such as a squeeze roll or a nip roll, the glass cloth tends to be less likely to break. Also, when the elastic modulus of the glass cloth is 70 GPa or less, the dielectric constant tends to be relatively lower. The elastic modulus can be measured by the method described in the examples. Also, the elastic modulus can be adjusted by the composition of the glass yarn.

[0049] The dielectric constant of the glass cloth of this embodiment is preferably 5.0 or less, more preferably 4.7 or less, further preferably 4.5 or less, and particularly preferably 4.0 or less, at a frequency of 1 GHz. In this embodiment, the dielectric constant refers to the dielectric constant at a frequency of 1 GHz, unless otherwise specified.

[0050] (composition) Glass yarn is obtained by bundling a plurality of glass filaments and twisting them as necessary, and glass cloth is obtained by weaving the above glass yarns as warp and weft. Glass yarns are classified into multifilament and glass filaments are classified into monofilament.

[0051] The average diameter of the glass filaments constituting the warp and weft is preferably 2.5 to 9 μm, more preferably 3.0 to 7.5 μm, and even more preferably 3.5 to 5.4 μm. When the average diameter of the glass filaments is within the above range, the processability of the obtained substrate tends to be improved when processed by a mechanical drill, a carbon dioxide gas laser, or a UV-YAG laser. Therefore, a thin and highly dense printed wiring board can be realized. In particular, when the average diameter is 5.4 μm or less, the surface area per unit volume increases, which tends to cause a decrease in strength due to heat treatment, so that the effect of suppressing the decrease in strength of this embodiment becomes more important. In addition, when the average diameter is 2.5 μm or more, the surface area is reduced, which suppresses the volatilization of the glass components, and in addition, in the glass cloth manufacturing process such as the fiber opening process and the surface treatment process, when the glass cloth passes through a squeeze roll, a nip roll, or the like in a wet state, breakage tends to be less likely to occur. Furthermore, in post-processes such as the production of prepregs, breakage tends to be less likely to occur when the glass cloth is passed through a slit for the purpose of controlling the amount of resin impregnated into the glass cloth.

[0052] The weft density of the warp and weft threads constituting the glass cloth is preferably 30 to 130 threads / 25 mm, more preferably 40 to 120 threads / 25 mm, and further preferably 50 to 110 threads / 25 mm.

[0053] The thickness of the glass cloth is preferably 8 to 100 μm, more preferably 10 to 50 μm, further preferably 12 to 35 μm, and most preferably 12 μm to 30 μm. When the thickness of the glass cloth is within the above range, a thin glass cloth with relatively high strength tends to be obtained. In particular, when the thickness is 8 μm or more, the proportion of glass filaments occupying the vicinity of the surface of the glass cloth decreases, so that the amount of volatilization of glass components tends to decrease. In addition, when the thickness is 100 μm or less, the proportion of glass filaments occupying the vicinity of the surface of the glass cloth increases, so that the strength is likely to decrease due to the increase in the amount of volatilization of glass components, and the effect of suppressing the decrease in strength of the present invention becomes more important. Note that the weight reduction coefficient depends on the diameter of the filaments constituting the glass cloth, and is therefore unlikely to depend on the thickness. This tendency is maintained at least within the above thickness range.

[0054] The fabric weight (weight) of the glass cloth is preferably 8 to 250 g / m 2 and more preferably 8 to 100 g / m 2 and more preferably 8 to 50 g / m 2 and particularly preferably 8 to 35 g / m 2 It is.

[0055] The weave structure of the glass cloth is not particularly limited, but examples thereof include plain weave, sash weave, satin weave, twill weave, etc. Among these, the plain weave structure is more preferable.

[0056] (Surface treatment) The glass cloth may be surface-treated with a surface treatment agent. The surface treatment agent is not particularly limited, but may be, for example, a silane coupling agent, and may be used in combination with water, an organic solvent, an acid, a dye, a pigment, a surfactant, or the like, as necessary.

[0057] The silane coupling agent is not particularly limited, but examples thereof include compounds represented by formula (1). X(R) 3-n SiY n (1) (In formula (1), X is an organic functional group having at least one of an amino group and an unsaturated double bond group, each Y is independently an alkoxy group, n is an integer of 1 to 3, and each R is independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group.)

[0058] X is preferably an organic functional group having at least three or more of amino groups and unsaturated double bond groups, and more preferably an organic functional group having at least four or more of amino groups and unsaturated double bond groups.

[0059] The alkoxy group may be in any form, but from the viewpoint of stabilizing the treatment of the glass cloth, an alkoxy group having 5 or less carbon atoms is preferred.

[0060] Specific examples of the silane coupling agent include N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropylmethyldimethoxysilane and its hydrochloride, N-β-(N-di(vinylbenzyl)aminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-di(vinylbenzyl)aminoethyl)-N-γ-(N-vinylbenzyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β Examples of known simple substances include -(N-benzylaminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-benzylaminoethyl)-γ-aminopropyltriisoethoxysilane and its hydrochloride, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltrimethoxysilane, methacryloxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and the like, or mixtures thereof.

[0061] The molecular weight of the surface treatment agent is preferably 100 to 600, more preferably 150 to 500, and further preferably 200 to 450. Among these, it is preferable to use two or more types of surface treatment agents having different molecular weights. By treating the surface of the glass yarn with two or more types of surface treatment agents having different molecular weights, the density of the surface treatment agent on the surface of the glass cloth tends to be increased, and the reactivity with the matrix resin tends to be further improved.

[0062] [Method of manufacturing glass cloth] The method for producing the glass cloth of the present embodiment is not particularly limited, but may include, for example, a method having a weaving step of weaving glass yarns to obtain a glass cloth, and a fiber-opening step of fiber-opening the glass yarns of the glass cloth. If necessary, the method may also have a desizing step of removing a sizing agent attached to the glass yarns of the glass cloth, and a surface treatment step using a surface treatment agent.

[0063] The weaving method is not particularly limited as long as it is a method of weaving the weft and warp to form a predetermined weave structure. The opening method is not particularly limited, but examples of the opening method include a method of processing the fibers with spray water (high pressure water opening), a vibro washer, ultrasonic water, a mangle, etc. Furthermore, the desizing method is not particularly limited, but examples of the method include a method of removing the sizing agent by heating. The surface treatment method includes a method of contacting the glass cloth with a surface treatment agent and drying, etc. The contact of the glass cloth with the surface treatment agent includes a method of immersing the glass cloth in the surface treatment agent, and a method of applying the surface treatment agent to the glass cloth using a roll coater, a die coater, a gravure coater, etc. The drying method of the surface treatment agent is not particularly limited, but examples of the drying method include hot air drying and drying using electromagnetic waves.

[0064] [Prepreg] The prepreg of the present embodiment includes the above-mentioned glass cloth and a matrix resin composition impregnated into the glass cloth. The prepreg including the above-mentioned glass cloth is less likely to cause a decrease in strength, and the yield of the final product is high. In addition, since the prepreg has excellent dielectric properties and excellent moisture absorption resistance, it is possible to provide a printed wiring board that is less susceptible to the influence of the usage environment, particularly in a high humidity environment, and has a small change in dielectric constant.

[0065] The prepreg of the present embodiment can be produced by a conventional method, for example, by impregnating the glass cloth of the present embodiment with a varnish prepared by diluting a matrix resin such as an epoxy resin with an organic solvent, volatilizing the organic solvent in a drying furnace, and curing the thermosetting resin to a B-stage state (semi-cured state).

[0066] Examples of the matrix resin composition include, in addition to the above-mentioned epoxy resins, thermosetting resins such as bismaleimide resins, cyanate ester resins, unsaturated polyester resins, polyimide resins, BT resins, and functionalized polyphenylene ether resins; thermoplastic resins such as polyphenylene ether resins, polyetherimide resins, liquid crystal polymers (LCPs) of wholly aromatic polyesters, polybutadiene, and fluororesins; and mixed resins thereof. From the viewpoint of improving dielectric properties, heat resistance, solvent resistance, and press moldability, the matrix resin composition may be a resin obtained by modifying a thermoplastic resin with a thermosetting resin.

[0067] The matrix resin composition may also contain inorganic fillers such as silica and aluminum hydroxide; flame retardants such as bromine-based, phosphorus-based, and metal hydroxides; other silane coupling agents; heat stabilizers; antistatic agents; ultraviolet absorbers; pigments; colorants; lubricants, etc.

[0068] [Printed Wiring Board] The printed wiring board of this embodiment includes the above-mentioned glass cloth. The printed wiring board of this embodiment is less likely to cause a decrease in strength, and the final product has a high yield. In addition, since the printed wiring board of this embodiment has excellent dielectric properties and excellent moisture absorption resistance, it can also have the effect of being less susceptible to the influence of the usage environment, particularly in a high humidity environment, and thus has a small change in the dielectric constant.

[0069] Unless otherwise specified, the various measurements described above are measured according to the measurement methods described in the Examples section below. EXAMPLES

[0070] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0071] [Physical properties of glass cloth] The physical properties of the glass cloth, specifically, the thickness of the glass cloth, the diameter of the filaments constituting the warp and weft, the number of filaments, and the weaving density (weaving density) of the warp and weft were measured in accordance with JIS R3420.

[0072] [Weight reduction coefficient] The weight loss coefficient was measured by the following procedure. First, the glass cloth pulled out from the intermediate roll was placed in a dryer at 105°C ± 5°C and dried for 60 minutes, then the glass cloth was transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth was measured to the nearest 0.1 mg (weight of glass cloth a). Next, the glass cloth was heated at 380°C for 2 hours, then the glass cloth was transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth was measured to the nearest 0.1 mg (weight of glass cloth after heat treatment b). Then, the weight reduction due to the heat treatment was determined, and the weight reduction ratio (%) was calculated using the following formula (2). Weight reduction rate (%) = (ab) / a×100 ···(2)

[0073] Next, the diameter of the monofilament was measured according to JIS R3420, Method B, and half of that value was defined as the radius of the monofilament. Although JIS R3420, Method B, requires that the diameters of 25 randomly selected filament cross sections be measured, the diameters of all the monofilaments constituting the glass yarn (multifilament) were measured, and the filament diameter was calculated as the average value. The weight loss coefficient was calculated from the weight loss rate (%) and the average radius (μm) of the glass filaments according to the following formula (1). Weight reduction coefficient = weight reduction ratio (%) × average radius of glass filaments (μm) (1)

[0074] [Elastic modulus] The elastic modulus of the glass yarn was measured by the pulse-echo overlap method using glass bulk as a test piece.

[0075] [Dielectric constant of glass yarn] The glass yarn was melted to prepare a bulk glass test piece with a length of about 50 mm and a width of about 1.5 mm, and the dielectric constant was measured using a cavity resonator. The test piece was placed in an oven at 105°C ± 2°C for 2 hours to dry, and then left in a thermostatic chamber at 23±2°C and a relative humidity of 50±5% for 96 hours, after which the dielectric constant at 10 GHz was measured.

[0076] The measurement was performed using a network analyzer (N5230A, manufactured by Agilent Technologies) and a cavity resonator (Cavity Resonator CP series) manufactured by Kanto Electronics Application Development Co., Ltd. under an environment of 23±2° C. and a relative humidity of 50±5%.

[0077] [Glass Cloth Composition] The composition of the glass cloth was measured by ICP atomic emission spectrometry. Specifically, the Si content and B content were measured by pressure-decomposing a weighed glass cloth sample with sodium hydroxide, dissolving it in dilute nitric acid, and filtering it. The insoluble matter was dissolved in sodium carbonate, combined with the filtrate, and the volume was determined. The obtained sample was measured by ICP atomic emission spectrometry.

[0078] The Fe, Al, Ca, and Ma contents were measured by decomposing the weighed glass cloth sample with perchloric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, then dissolving it by heating with dilute aqua regia and filtering it. The filtrate was made to a constant volume. The insoluble matter was decomposed with sulfuric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, and dissolved to a constant volume. The obtained sample was measured by ICP atomic emission spectrometry. The ICP atomic emission spectrometry was performed using a PS3520VDD II manufactured by Hitachi High-Tech Science Corporation.

[0079] Furthermore, the F content was measured by burning a weighed glass cloth sample in a tubular electric furnace, and then absorbing the generated gas into an absorbing solution. The solution was analyzed by ion chromatography to determine the amount of fluoride ions (F - The content in the sample was calculated by measuring the amount of benzene in the sample. The combustion apparatus used was an automatic sample combustion apparatus (AQF-2100S) manufactured by Mitsubishi Chemical Analytech Co., Ltd., and the measurement apparatus used was an ion chromatograph ICS-1500 manufactured by Thermo Fisher Scientific Co., Ltd.

[0080] [Strength reduction confirmation test] Using the glass cloth obtained in the examples and comparative examples, prepregs were produced under the following conditions, and the strength was evaluated to see if it was sufficient. The glass cloth was continuously drawn out and conveyed, and the glass cloth was immersed in varnish and passed through a slit to adjust the amount of varnish applied. The glass cloth was then dried in a drying oven at 120°C to obtain a prepreg. The varnish used contained 65 parts by mass of methacrylated polyphenylene ether, 35 parts by mass of triallyl isocyanurate, 10 parts by mass of hydrogenated styrene-based thermoplastic elastomer, 25 parts by mass of bromine-based flame retardant, 65 parts by mass of spherical silica, 1 part by mass of organic peroxide, and 210 parts by mass of toluene.

[0081] For each of the glass cloths obtained in the Examples and Comparative Examples, ten product rolls of 2000 m each were fabricated into prepregs by the above-mentioned method. Based on the fabrication results, the strength reduction was confirmed according to the following evaluation criteria. ◎: When the glass cloth was not broken and prepreg could be produced using 10 glass cloth rolls, the glass cloth was judged to be excellent in productivity and handling. Good: In the process of making the prepreg, one glass cloth roll broke, but the remaining nine rolls were able to make the prepreg without breaking. It was determined that the glass cloth had sufficient strength for practical use. △: In the process of producing the prepreg, breakage occurred in 2 to 3 glass cloth rolls, but the remaining rolls were able to produce prepreg without breakage. It was determined that the glass cloth needed to be improved in strength. ×: Breakage occurred in four or more glass cloth rolls during the prepreg manufacturing process.

[0082] [Dielectric constant and dielectric loss tangent of laminate] A predetermined number of prepregs obtained in the strength reduction confirmation test were stacked so that the thickness of the laminate was about 1 mm, and copper foil (GTS-MP foil, 18 μm thick, manufactured by Furukawa Electric Co., Ltd.) was placed on both sides of the stacked prepregs, and the laminate was obtained by vacuum pressing. Next, the copper foil was removed from the copper clad laminate by etching, to obtain a laminate.

[0083] A test piece of about 50 mm in length and about 1.5 mm in width was cut out from the obtained laminate so that the warp threads of the glass cloth were the long side, and used as a test piece for electrical property testing. The obtained test piece was placed in an oven at 105°C ± 2°C and dried for 2 hours, and then the dielectric constant and dielectric loss tangent at 10 GHz were measured under the standard conditions and high humidity conditions shown below. Standard conditions: Measured after leaving in a constant temperature room at 23±2℃ and relative humidity of 50±5% for 96 hours High humidity conditions: Measured after leaving the material in a constant temperature room at 40±2℃ and 85±5% relative humidity for 96 hours.

[0084] The measurement was performed using a network analyzer (N5230A, manufactured by Agilent Technologies) and a cavity resonator (Cavity Resonator CP series) manufactured by Kanto Electronics Application Development Co., Ltd., in an environment of 23±2°C and relative humidity of 50±5%. Each measurement was repeated five times using five cut-out test pieces, and the average values ​​were used as the dielectric constant and dielectric loss tangent.

[0085] Example 1 A low dielectric glass yarn (dielectric constant 4.8) consisting of 50 filaments with an average filament diameter of 4.0 μm was woven by an air jet loom to obtain a glass cloth with a warp and weft density of 94 / 25 mm and a thickness of 14 μm. The glass cloth was then desizing processed by heating to obtain an intermediate glass cloth roll with a width of 1280 mm and a length of 2000 m.

[0086] The obtained glass cloth intermediate roll was used to continuously pull out and transport the glass cloth from the glass cloth intermediate roll, while immersing the glass cloth in a treatment liquid containing a silane coupling agent, adjusting the amount of the silane coupling agent applied by squeezing the liquid, and then drying it once. Next, the glass cloth was opened by a high-pressure water spray, dried, and wound into a roll to obtain a glass cloth product roll. The above-mentioned application of the silane coupling agent and the opening treatment were performed continuously for 10 rolls. The composition of the obtained glass cloth was as shown in Table 1.

[0087] [Examples 2 to 11] Except for the different composition of the glass yarn, a roll of glass cloth was obtained in the same manner as in Example 1. The composition of the obtained glass cloth was as shown in Table 1.

[0088] Example 12 A roll of glass cloth was obtained in the same manner as in Example 2, except that the same low dielectric glass yarn as in Example 2 was used and the degree of spreading was reduced by weakening the strength of the high-pressure water spray in the spreading process.

[0089] Example 13 A roll of glass cloth was obtained in the same manner as in Example 2, except that the same low dielectric glass yarn as in Example 2 was used and the degree of fiber spreading was increased by increasing the intensity of the high-pressure water spray in the fiber spreading process.

[0090] Example 14 A roll of glass cloth was obtained in the same manner as in Example 1, except that a low dielectric glass yarn (dielectric constant 4.8) consisting of 100 filaments with an average filament diameter of 5.0 μm was woven to produce a glass cloth with a warp and weft pick density of 69 yarns / 25 mm. The thickness of the obtained glass cloth was 30 μm, and the composition was as shown in Table 1.

[0091] Example 15 A roll of glass cloth was obtained in the same manner as in Example 14, except that the packing density of the warp and weft was set to 55 yarns / 25 mm. The thickness of the obtained glass cloth was 30 μm, and the composition was as shown in Table 1.

[0092] Example 16 A roll of glass cloth was obtained in the same manner as in Example 1, except that a low dielectric glass yarn (dielectric constant 4.8) consisting of 200 filaments with an average filament diameter of 7.0 μm was woven to prepare a glass cloth with warp and weft pick densities of 60 / 25 mm and 57 / 25 mm, respectively. The thickness of the obtained glass cloth was 92 μm, and the composition was as shown in Table 1.

[0093] [Comparative Examples 1 to 6] Except for the different composition of the glass yarn, a roll of glass cloth was obtained in the same manner as in Example 1. The composition of the obtained glass cloth was as shown in Table 1.

[0094] [Reference example 1] A roll of glass cloth was obtained in the same manner as in Example 1, except that glass yarn of E glass composition (dielectric constant 6.8) was used.

[0095] [Table 1]

[0096] [Table 2]

[0097] The glass cloths of Examples 1 to 4, 7, 12, and 14 to 16 could be stably produced without breakage of the glass cloth in all 10 rolls. In addition, the glass cloths of Examples 5, 6, 8 to 11, and 13 broke in only one roll, but the remaining nine rolls could be stably produced. In addition, the glass cloth of Reference Example 1 did not break, but had poor electrical properties.

[0098] On the other hand, the glass cloths of Comparative Examples 1, 3, and 5 broke on the second or third roll. This is insufficient for stably supplying printed wiring boards using low dielectric glass, and improvement is required. Furthermore, the glass cloths of Comparative Examples 2, 4, and 6 broke on four consecutive rolls from the start of coating, so the coating test had to be stopped.

[0099] Furthermore, as shown in Example 11, it was found that when the Mg content was high, the increase in the dielectric loss tangent under high humidity conditions was large when the laminate was made. [Industrial Applicability]

[0100] INDUSTRIAL APPLICABILITY The present invention has industrial applicability as a low dielectric glass cloth used for prepregs and the like.

Claims

1. A glass cloth constructed by using glass yarns made of a plurality of glass filaments as warp yarns and weft yarns, In the following formula (1), a weight reduction coefficient calculated as the product of the weight reduction rate derived from the glass component in a heat treatment at 380° C. for 2 hours and the average radius of the glass filaments is 0.18 or more and 0.45 or less, Weight reduction coefficient=weight reduction ratio (%)×average radius of the glass filaments (μm) (1) The Fe content of the glass cloth is Fe 2 O 3 In terms of mass percent, it is more than 0.1% and less than 0.4% by mass. Glass cloth.

2. The Fe content of the glass cloth is Fe 2 O 3 In terms of mass percent, it is more than 0.2 mass% and less than 0.4 mass%. The glass cloth according to claim 1.

3. The Fe content of the glass cloth is Fe 2 O 3 In terms of mass percent, it is more than 0.3 mass% and less than 0.4 mass%. The glass cloth according to claim 2.

4. The F content of the glass cloth is more than 0.005% by mass and less than 0.4% by mass. The glass cloth according to any one of claims 1 to 3.

5. The F content of the glass cloth is more than 0.005% by mass and less than 0.2% by mass. The glass cloth according to claim 4.

6. The F content of the glass cloth is more than 0.005% by mass and less than 0.1% by mass. The glass cloth according to claim 5.

7. The glass cloth, The Si content is SiO 2 In terms of mass conversion, it is 40 to 60 mass%, B content is B 2 O 3 In terms of mass conversion, it is 15 to 30 mass%. The glass cloth according to any one of claims 1 to 6.

8. The glass cloth, The Al content is Al 2 O 3 In terms of mass conversion, it is 10 to 20 mass %, The Ca content is 4 to 12 mass% in terms of CaO, The Mg content is 1% by mass or less in terms of MgO. The glass cloth according to claim 7.

9. The elastic modulus of the glass cloth is 50 to 70 GPa. The glass cloth according to any one of claims 1 to 8.

10. The elastic modulus of the glass cloth is 50 to 63 GPa. The glass cloth according to claim 9.

11. The average diameter of the glass filaments constituting the warp and weft yarns is independently 3.5 to 5.4 μm. The glass cloth according to any one of claims 1 to 10.

12. having a dielectric constant of 5.0 or less at a frequency of 1 GHz; The glass cloth according to any one of claims 1 to 11.

13. The glass cloth according to any one of claims 1 to 12, and a matrix resin impregnated in the glass cloth. Prepreg.

14. The glass cloth according to any one of claims 1 to 12 is provided. Printed wiring board.

Citation Information

Patent Citations

  • Low dielectric constant glass fiber

    JP1999292567A